UJI EFEKTIVITAS ANTIMIKROBA DARI FORMULASI EKSTRAK DAUN KEMANGI (Ocinum basilicum L.) DAN DAUN RAMBUTAN (Nephelium lappaceum L.) TERHADAP BAKTERI Staphylococcus aureus - Muhammad Rizky Dwinarta; Zulkifli Lubis (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
This research was conducted to determine whether the formulation of the two kind of leaves affects the growth of Staphylococcus aureus bacteria which generally attack high protein foods such as fish and meat. This studied uses a diffusion method with paper discs consisted of 5 levels, namely A = 80%: 20%, B = 60%: 40%, C = 50%: 50%, D = 40%: 60%, E = 20 %: 80% and 2 extract controls namely 100% basil extract control and 100% rambutan extract control. The parameters in this studied were to saw the effectiveness of antimicrobial compound formulations by means of measured the diameter of the inhibitory zone produced, and the level of antimicrobial strength in this studied was still weak because the test bacteria were stronger than the formulations given. The diffusion method used in this study is to homogenize the bacterial suspension with a boilon solution, then pour it into a cup that contains NA medium, then etch it gently on the surface of the media and put disc paper that has been given a formulation solution. Perform incubation for 24 hours at a temperature of 370C then measuring the inhibitory zone formed to determined the effectiveness of antimicrobial formulations.